2022
DOI: 10.1371/journal.pone.0273735
|View full text |Cite
|
Sign up to set email alerts
|

Relative impact of genetic ancestry and neighborhood socioeconomic status on all-cause mortality in self-identified African Americans

Abstract: Self-identified race/ethnicity is a correlate of both genetic ancestry and socioeconomic factors, both of which may contribute to racial disparities in mortality. Investigators often hold a priori assumptions, rarely made explicit, regarding the relative importance of these factors. We studied 2,239 self-identified African Americans (SIAA) from the Prostate, Lung, Colorectal and Ovarian screening trial enrolled from 1993–1998 and followed prospectively until 2019 or until death, whichever came first. Percent A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 71 publications
3
15
0
Order By: Relevance
“…The 21% reduction in screening encountered in our own data appears consistent with the latter published reports and endorses the external validity of our findings. Similarly, the reduced use of screening among individuals of lower socioeconomic class, Asian, and the Native American population prior to the pandemic is aligned with other reports from this period 6–8,26 …”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The 21% reduction in screening encountered in our own data appears consistent with the latter published reports and endorses the external validity of our findings. Similarly, the reduced use of screening among individuals of lower socioeconomic class, Asian, and the Native American population prior to the pandemic is aligned with other reports from this period 6–8,26 …”
Section: Discussionsupporting
confidence: 69%
“…Similarly, the reduced use of screening among individuals of lower socioeconomic class, Asian, and the Native American population prior to the pandemic is aligned with other reports from this period. [6][7][8]26 Outside of our determinations regarding reduced colorectal screening overall, the most concerning findings are those that indicate persistent disparities in the use of these services among African Americans, Asians, Pacific Islanders, and Native Americans/Alaskans, as well as individuals of lower socioeconomic backgrounds. Worsening disparities among Native Americans/Alaskans, based on socioeconomic status, were also evident in the pandemic period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that African genetic ancestry was correlated with TNBC in unadjusted models, but this association attenuated to the null following adjustment for nSES. In a secondary analysis of 2239 Black men and women in the Prostate, Lung, Colorectal, and Ovarian cancer screening trial, associations between African genetic ancestry, nSES, and overall mortality found that although African ancestry was initially associated with higher all-cause mortality, this association attenuated following adjustment for lifestyles and comorbidities . Similarly, no associations were observed between African ancestry and cancer-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…While available evidence suggests both genetic and environmental factors may explain excess mortality in Black women, few studies have incorporated them in their design and analysis . Failure to account for both genetic and nSES factors may lead to overestimates of their relative importance . To address these gaps, we examined joint associations of African ancestry (representing genetic influences) and nSES (representing environmental influences) on tumor aggressiveness and mortality in a large, population-based cohort of Black female breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%